2012
DOI: 10.1590/s1806-37132012000600011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da utilidade diagnóstica da fibrobroncoscopia óptica na tuberculose pulmonar BAAR negativa na prática clínica de rotina

Abstract: We evaluated the diagnostic yield of fiberoptic bronchoscopy for the diagnosis of smear-negative pulmonary tuberculosis in patients treated at a referral hospital in Lima, Peru. Of the 611 patients who underwent the procedure, 140 (23%) were diagnosed with tuberculosis based on the analysis of BAL samples. Being young and being male were significantly associated with positive cultures. In addition, 287 patients underwent postbronchoscopic sputum smear testing for AFB, the results of which increased the diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…The frequency of pneumocystis pneumonia, nocardiosis and fungal infections was much higher in our study, totaling 21.86%, compared to that reported by others 8 for the same reason, i.e., we selected HIV-immunosuppressed patients who are known to have a higher frequency of these opportunistic infections. In a study carried out in a referral hospital in Lima, Peru 7 , the authors have also found a higher frequency of tuberculosis (23%) in the studied bronchoalveolar lavage samples. The patients of that study were also selected based on clinical suspicions of tuberculosis.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The frequency of pneumocystis pneumonia, nocardiosis and fungal infections was much higher in our study, totaling 21.86%, compared to that reported by others 8 for the same reason, i.e., we selected HIV-immunosuppressed patients who are known to have a higher frequency of these opportunistic infections. In a study carried out in a referral hospital in Lima, Peru 7 , the authors have also found a higher frequency of tuberculosis (23%) in the studied bronchoalveolar lavage samples. The patients of that study were also selected based on clinical suspicions of tuberculosis.…”
Section: Discussionmentioning
confidence: 69%
“…Another important point is the technique used for the diagnosis. We performed the direct search of microorganisms in liquid or tissue samples through special staining methods such as Fite Faraco and Ziehl-Neelsen; other authors used culture and/or PCR techniques to search for etiological agents, thus increasing the chances of reaching a diagnosis 7,8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, it is thought that microbiological examination of bronchial aspirate and BAL are positive for Mycobacterium tuberculosis in patients with EBTB, and that examination provides a good diagnostic yield [ 14 ]. A study conducted by Ozkaya et al highlights the difficulty of the bacteriological diagnosis of EBTB based on BAL analysis, bronchial aspirate, or sputum analysis, and showed that a high diagnostic yield was obtained through the histopathologic examinations of bronchial biopsies, confirmed in our clinical case [ 15 ].…”
Section: Discussionmentioning
confidence: 99%